Bar Wars: Changing Geographies of Gender in Spain - David Gilmore (Masculinities and Social Change, 2012)
This paper looks at gender segregation in rural Spain from an historical viewpoint. The subject is gender apartheid: female seclusion and male dominance in public places and the vicissitudes therein. The paper shows how a venerable pattern of female seclusion has been challenged and describes what the social consequences cultural are of this cultural upheaval. Working from the premise of public/private? as ethnographically valid, the author describes how women in Andalusia have created a new institution specifically designed to breech the barriers of masculine space and attain public access.